2011
DOI: 10.1111/j.1445-6664.2011.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of wild barley (Hordeum spontaneum) and winter wheat (Triticum aestivum) to sulfosulfuron: The role of degradation

Abstract: Wild barley (Hordeum spontaneum) is one of the most troublesome weed species in winter wheat (Triticum aestivum) in Iran.Two bioassay experiments were conducted in order to study the response of wild barley and wheat to different herbicides and to study the efficacy of pre-emergence (PRE), postemergence (POST), and PRE followed by POST applications of sulfosulfuron on wild barely. Moreover, the degradation of sulfosulfuron was studied by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Park et al (2004) observed that 80% of the absorbed 14 C-propoxycarbazone was metabolized in susceptible and resistant biotypes of downy brome (Bromus tectorum L.), but resistant biotypes had more rapid metabolism. Similar differences in metabolism have been noted in tolerant and susceptible species for other ALS inhibitors including chlorsulfuron, procarbazone, primsulfuron, sulfosulfuron, and trifloxysulfuron (Fandrich et al 2001;Hoseeini et al 2011;Mekki and Leroux 1995;Richardson et al 2003).…”
Section: Specific Radioactivity Species Asupporting
confidence: 62%
“…Park et al (2004) observed that 80% of the absorbed 14 C-propoxycarbazone was metabolized in susceptible and resistant biotypes of downy brome (Bromus tectorum L.), but resistant biotypes had more rapid metabolism. Similar differences in metabolism have been noted in tolerant and susceptible species for other ALS inhibitors including chlorsulfuron, procarbazone, primsulfuron, sulfosulfuron, and trifloxysulfuron (Fandrich et al 2001;Hoseeini et al 2011;Mekki and Leroux 1995;Richardson et al 2003).…”
Section: Specific Radioactivity Species Asupporting
confidence: 62%
“…There are direct and indirect methods to identify whether herbicide metabolism is involved in crop tolerance. Direct methods involve chromatography to evaluate the decomposition of the herbicide and/or the formation of the metabolites (Hosseini et al, 2011;Yu and Powles, 2014). Indirect methods may involve the use of inhibitors of herbicide detoxification, such as malathion and chlorpyrifos (Kaspar et al, 2011;Beckie et al, 2012), or the use of stimulators of herbicide metabolization, also called crop safener (Bunting et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibited growth and biomass reduction due to exposure of herbicide mixtures was recovered by wheat plant and no significant effect was observed at maturity (Table 5). Recovery to phytotoxic effects of herbicides has been reported for wheat plant by Hosseini et al (2011) and Bhullar et al (2012).…”
Section: Effect Of Mixtures Application On Grain Yield and Yield Contmentioning
confidence: 96%